Effect of CPAP therapy on endothelial function in obstructive sleep apnoea: A systematic review and meta-analysis - Schwarz, E; Puhan, M; Schlatzer, C; Stradling, J; Kohler, M; Kohler, M (2015)
© 2015 Asian Pacific Society of Respirology. Obstructive sleep apnoea (OSA) is a prevalent sleep-related breathing disorder associated with adverse cardiovascular outcome. Endothelial dysfunction is one of the proposed mechanistic links between OSA and the increased cardiovascular risk. Treatment with continuous positive airway pressure (CPAP) may reverse this detrimental pathophysiological consequence of OSA. Most studies on the effect of CPAP on endothelial function in OSA are limited by their low sample size. The objective of this systematic review was to assess the effect CPAP therapy on endothelial function in patients with OSA. We conducted a systematic review and meta-analysis searching literature databases up to August 2013 for randomized controlled trials (RCTs) on the effect of CPAP on endothelial function in OSA, assessed by flow-mediated dilatation (FMD) and other validated techniques. The primary outcome for the meta-analysis (DerSimonian/Laird random-effects method) was the treatment effect on FMD. Eight RCTs comparing the effects of therapeutic CPAP versus subtherapeutic CPAP (or no intervention) on endothelial function involving 245 OSA patients were included in the systematic review. The studies are consistent in effect direction, showing an improvement of endothelial function by CPAP. Four RCTs involving 150 patients could be used for the meta-analysis. Compared to the control group, CPAP therapy (range 2-24 weeks) significantly increased absolute % FMD by 3.87% (95% confidence interval: 1.93-5.80, P < 0.001). In patients with OSA, CPAP therapy improves endothelial function significantly and to a clinically important extent.